Pengaruh Promosi Dan Lokasi Terhadap Minat Beli Konsumen Toko Swalayan Mitra Mart Tasikmalaya : (Survei Pada Konsumen Toko Swalayan Mitra Mart Kota Tasikmalaya) - Rizal Anugrah Holiq (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
The purpose of this study was to determine the effect of Promotion and Location simultaneously or partially on the Consumer Buying Interest of the Mitra Mar shopt, a survey on the consumer of the Mitra Mart in Tasikmalaya City. The research method used is a survey method with a quantitative approach. The sample in this study amounted to 100 respondents. Data collection was done by using a questionnaire. The data collected in the form of primary data. Data analysis in this study used multiple regression analysis, correlation coefficient and coefficient of determination using SPSS software. The results of this study show that simultaneously promotion and location have a significant effect on consumers buying interest at the Tasikmalaya City Mitra Mart Shop. Partially promotion has a significant effect on consumer buying interest. Partially, location has a significant effect on consumer buying interest.